Relationship Between Hamstring Flexibility and Extensor Muscle Activity During a Trunk Flexion Task - Nikzad, Sousan (J Chiropr Med, 2020)
OBJECTIVE: The purpose of this study was to investigate the relationship between hamstring flexibility and electromyography (EMG) muscle parameters in back and lower limb extensor muscles during a trunk flexion task. METHODS: Thirty healthy women aged 18 to 30 years with normal hip movement were recruited for this study. Hamstring muscle flexibility was measured with the 90-90 active straight leg raise test. Surface EMG activities were simultaneously recorded from the lumbar erector spinae, gluteus maximus, biceps femoris, semitendinosus, lateral gastrocnemius, and medial gastrocnemius muscles during forward bending. Muscle activity onset and offset, amplitude, and duration were calculated with technical computer software (MATLAB, version 1.6.0). Linear regression analysis was used to investigate the relationships between hamstring flexibility test results and EMG parameters during trunk flexion. In addition, the Friedman test was used to determine the recruitment activity pattern in women with low versus normal hamstring flexibility. RESULTS: During flexion, the back extensor muscles in individuals with lower hamstring flexibility test scores were activated and deactivated later, which can lead to delayed flexion-relaxation. Regression analysis did not disclose any significant correlations between hamstring flexibility and other EMG parameters (duration and amplitude) in back extensor muscles. Activation and deactivation recruitment patterns differed between the groups with normal and low hamstring flexibility. CONCLUSION: The findings of this study suggest that hamstring flexibility plays an important role in the patterns of trunk and lower limb muscle activity onset, offset, and recruitment.